Synthesis and Neurotrophic Activity Studies of Illicium Sesquiterpene Natural Product Analogues. Issue 13 (7th February 2017) - Richers, Johannes; Pöthig, Alexander; Herdtweck, Eberhardt; Sippel, Claudia; Hausch, Felix; Tiefenbacher, Konrad
Abstract: Neurotrophic natural products hold potential as privileged structures for the development of therapeutic agents against neurodegeneration. However, only a few studies have been conducted to investigate a common pharmacophoric motif and structure–activity relationships (SARs). Here, an investigation of structurally more simple analogues of neurotrophic sesquiterpenes of the illicium family is presented. A concise synthetic route enables preparation of the carbon framework of (±)‐Merrilactone A and (±)‐Anislactone A/B on a gram scale. This has allowed access to a series of structural analogues by modification of the core structure, including variation of oxidation levels and alteration of functional groups. In total, 15 derivatives of the natural products have been synthesized and tested for their neurite outgrowth activities. Our studies indicate that the promising biological activity can be retained by structurally simpler natural product analogues, which are accessible by a straightforward synthetic route. Abstract : Stripped‐down sesquiterpenes : Access to a series of structural analogues of the illicium sesquiterpene natural products (±)‐Merrilactone A and (±)‐Anislactone A/B (see graphic; left) is enabled by an efficient synthetic route. The derivatives can be prepared in six to eight steps and retain biological activity, as shown in neurite outgrowth studies (see graphic; right).